Urgensi Indigenous Psychology: Mindfulness sebagai Upaya Menemukan Kabegjan - Malik Septian Ardi Nugraha; Martinus Suharsono (Bulletin of Community Engagement, 2024)
Subjective happiness has become a very popular topic this decade in psychological research. In addition to the many definitions of happiness, the author sees a common agreement that happiness or subjective well-being is influenced by the culture where a person comes from. Therefore, here the author uses a local definition of happiness, namely kabegjan conveyed by Ki Ageng Suryamentaram, where kabegjan itself is formed in the context of life that is mulur-mungkret in each individual. Raos begja was constructed by Suryomentaram, and is also closely related to the authentic happiness paradigm, as well as the subjective well-being paradigm. Raos begja can be achieved when individuals are able to implement kawruh begja (knowledge of happiness). This kawruh begja paradigm is compiled in kawruh begja sawetah (knowledge of complete happiness). The author uses literature review techniques from several studies with the keywords indigenous psychology, happiness, and mindfulness that have been published in accredited journals, in this study the author sees that the ability to interpret happiness (kabegjan) is also very closely correlated with the ability to be mindful.